PENGARUH MODAL USAHA, LITERASI KEUANGAN DAN PENGGUNAAN SOCIAL COMMERCE TERHADAP KEBERLANJUTAN USAHA MIKRO, KECIL DAN MENENGAH DI KECAMATAN BULELENG - Kadek Windayani Purnama Dewi; Nyoman Trisna Herawati (Universitas Pendidikan Ganesha, 2023)
This study aims to determine the positive and significant influence of business capital, financial literacy and the use of social commerce on the sustainability of micro, small and medium enterprises in Buleleng District. The population of this study is MSME actors who already have business licenses and are registered in Dinas Perdagangan, Perindustrian dan Koperasi, UKM Kabupaten Buleleng and total is 842 businesses. The sampling technique used was purposive sampling and the slovin formula as many as 89 respondents. Research data collection was carried out using questionnaires which were distributed directly and through Google forms. Data analysis techniques in this study consisted of descriptive statistical analysis, data quality testing, classical assumption testing, multiple linear regression analysis and hypothesis testing using the SPSS v.20 program. The results of the study show that (1) business capital has no effect on business continuity, (2) financial literacy has a positive and significant effect on business continuity and (3) the use of social commerce has a positive and significant effect on business continuity.